A one-year practice-based learning programme for new general practice nurses in Scotland: evaluation of the pilot. Issue 1 (2nd January 2016) - Wakeling, Judy; Ferguson, Julie; Kennedy, Susan
Abstract: This paper summarises the evaluation of a pilot programme introduced by NHS Education for Scotland to provide education and skills training for nurses new to general practice. The programme was developed through extensive consultation with existing general practice nurses and was educationally accredited by the Royal College of General Practitioners and the Royal College of Nursing in 2013. Twelve nurses embarked upon the programme 2012–2013 and nine completed it. The programme was extensively evaluated through questionnaires (with supervisors, practice staff and participants), analysis of programme documentation and interviews with participants. Based on the evaluation feedback, alterations have been made to subsequent deliveries of the programme. These include removing some topic areas and lengthening the programme by three months. The programme continues to be successfully delivered and evaluation is ongoing to ensure it continues to meet nurses' needs.